Viscometric Study of Pectin. Effect of Temperature on the Hydrodynamic Properties - Masuelli, Martin Alberto (2011)
Hydrodynamic properties are important parameters affecting the performance of pectin. This polysaccharide is used as a thickening and gelling agent in food and pharmaceutical industries. The most common and economical of the hydrodynamic properties is the determination of viscosity, in which are determined the intrinsic viscosity and the diffusion coefficient. They indirectly measure the molecular weight (Mw); hydrodynamic radius (RH); number of Simha, (ν(a/b)); Perrin parameter (P); Scheraga-Mandelkern parameter (β); and Flory parameters (φ0 and P0). All the hydrodynamic parameters are dependent on temperature. Normally these parameters are reported at a temperature of 25°C, which limits their application to different temperatures. This work studies pectin dependence on temperature, finding that this biopolymer in aqueous solution presents a conformation of rod-like with ν(a/b)=10.5, and a value from 0.8232 to 0.8129. Pectin behavior in this system indicates that it behaves like a colloidal particle that tends to compact with increasing temperature (RH decrease). The molecular weight calculated for pectin is 180,000g/mol. Mark-Houwink-Sakurada (M-H-S) equation constants, a and k, for pectin in water solvent-temperature systems have been already reported.